Are Mauritia flexuosa L. f. palm swamps in the Brazilian Pantanal true veredas? A floristic appraisal - Moreira, Suzana Neves; Pott, Vali Joana; de Souza, Evaldo Benedito; Pott, Arnildo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
In this first report on the flora of Mauritia flexuosa L. f. palm swamps in the Pantanal wetland of Brazil, we surveyed and compared the angiosperm flora of eight areas of palm swamps in the Pantanal plain to determine if they correspond to veredas. Studied areas were four sites near the upland in Rio Verde and Coxim, and four in the Parque Estadual do Pantanal do Rio Negro, Aquidauana, state of Mato Grosso do Sul, Brazil. To determine species similarity, we compared our results with inventories of aquatic plants of the Pantanal and of species of veredas in the state. Using the wandering method, we recorded a total of 385 species of phanerogams. Species richness was higher in Rio Verde/Coxim (273 species) than in Rio Negro (243 species), with a similarity of 33.7%. We found a rare and endemic plant, Polygala grazielae Marques, first record in the Pantanal. We found that both sites correspond to two types of palm swamps but with different floras. The species associated with M. flexuosa in the park are much the same as those of seasonally flooding grasslands of the Pantanal, while on the edge of the plain many species are common to the upland true veredas, particularly on organic soil. Thus, we conclude that the Rio Verde/Coxim areas are true veredas. These palm swamps and veredas in the Pantanal should receive the same legal protection as the veredas in Cerrado.
Keywords: Moriche palm, Flora, Grassland, Polygala, Savanna, Wetland